Case Report: Leadless and left bundle branch area pacemakers, complementary advantages require a personalized approach - Yousuf, Omair; Lee, Jae (Jeff); Atwater, Brett D. (Frontiers in Cardiovascular Medicine, 2024)
Traditional transvenous pacemakers are composed of a pacemaker generator usually positioned surgically in the left upper chest on the pectoral muscle fascia and one or more leads positioned through the veins to the right atrium and across the tricuspid valve to the right ventricular apex. While these devices reduce symptoms and improve survival for patients with symptomatic bradycardia, they are associated with increased risk of infection, venous occlusion, heart failure, and tricuspid valve regurgitation. New pacemaker designs minimize these risks but no current generation pacemaker designs effectively eliminate all these risks. A personalized approach to the decision of which pacemaker is appropriate for an individual patient is needed to optimize outcomes.